Hes1, a new target for interleukin 1β in chondrocytes. Issue 8 (12th November 2009) - Ottaviani, Sebastien; Tahiri, Khadija; Frazier, Aline; Hassaine, Zohra Nabila; Dumontier, Marie-France; Baschong, Werner; Rannou, François; Corvol, Marie-Therese; Savouret, Jean-François; Richette, Pascal
Abstract : Objectives: To investigate the effects of interleukin 1β (IL1β) treatment on the Notch1/Hes1 pathway in chondrocytes in vitro. Methods: Mouse articular chondrocytes in primary culture were challenged with IL1β, alone or combined with Notch1 and IL1β pathway inhibitors. Notch1 and Hes1 expressions were investigated by immunocytochemistry, western blot and real-time quantitative (q)PCR. IL1β-responsive genes were assessed by real-time qPCR and a specific siRNA against Hes1 was used to identify Hes1 target genes. Results: Notch1 labelling remained nuclear and stable in intensity irrespective of treatment, suggesting a steady state activation of this pathway in our model. IL1β transiently increased Hes1 mRNA (2.5-fold) and protein expression in treated versus naive chondrocytes. Hes1 mRNA level then decreased below control and its cyclic pattern of expression was lost. This was associated with nuclear translocation of the cytoplasmic Hes1 protein. IL1β induced increase in Hes1 mRNA was transcriptional, occurred through nuclear factor (NF)κB activation and appeared to be associated with downregulation by its own protein. Hes1 induction was insensitive to the γ-secretase inhibitor N -( N -(3, 5-difluorophenacetyl)-l-alanyl)- S -phenylglycine t -butyl ester (DAPT), which suggested its independence from novel Notch1 activation. Hes1 expression was efficiently silenced by a specific siRNA. This experiment revealed that Hes1 did not mediate IL1β-induced downregulation of Sox9, type II collagen and aggrecan transcription but mediated IL1β induction of matrix metalloproteinase (MMP)13 and ADAM metallopeptidase with thrombospondin type 1 motif, 5 (ADAMTS5). The Hes1-related repressor Hey1 was expressed at a very low level and was not inducible by IL1β. Conclusion: Hes1 is a novel IL1β target gene in chondrocytes which influences a discrete subset of genes linked to cartilage matrix remodelling and/or degradation.